The Effect of Using English Songs by Olivia Dean through Spotify on Students’ Vocabulary Mastery at Vocation High School - Raifhannisa Adiibah Alvan; Ade Ismail Ramadhan Hamid; Abdul Halim (Universitas Islam Negeri Palopo, 2026)
This study aims to investigate the effect of using English songs by Olivia Dean through Spotify on students’ vocabulary mastery at SMK Negeri 1 Tenggarong. Vocabulary mastery is an essential component for supporting both academic achievement and workplace communication in vocational contexts, yet conventional instruction often lacks engagement. This study employed a quantitative one-group pre-experimental pretest–posttest design involving 34 eleventh-grade students from the Accounting and Financial Institution program selected through purposive sampling. The instrument was a fill-gap lyric vocabulary test based on the song “So Easy (To Fall In Love).” Data were collected through a pretest, four treatment sessions, and a posttest, and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results show a significant improvement in students’ vocabulary mastery, with mean scores increasing from 57.06 in the pretest to 92.35 in the posttest (Z = -5.125, p < 0.05, r = 0.879). The effect size indicates a very strong impact. These findings demonstrate a significant pedagogical impact of integrating structured song-based instruction through digital platforms. In practice, vocational EFL teachers can incorporate lyric-based listening activities and repeated exposure through streaming platforms to support effective and engaging vocabulary learning.